2012
DOI: 10.1177/1750635211434373
|View full text |Cite
|
Sign up to set email alerts
|

What’s love got to do with it? Framing ‘JihadJane’ in the US press

Abstract: The purpose of this article is to compare and contrast the US press coverage accorded to female terrorist plotter, Colleen LaRose, with that of two male terrorist plotters in order to test whether assertions in the academic literature regarding media treatment of women terrorists stand up to empirical scrutiny. The authors employed TextSTAT software to generate frequency counts of all words contained in 150 newspaper reports on their three subjects and then slotted relevant terms into categories fitting the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
2
17
0
2
Order By: Relevance
“…Moreover, information was given regarding their motives, which were mostly ideological, but also more mental and personal than for men. These findings correspond to the framing modes described by Nacos (2005) and Conway and McInerney (2012), regarding how the media portrays female terrorists. More specifically, two main framing modes are salient for our findings: The family connection frame, emphasizing familial status; and the bored, naive, out-of-touch-with-reality frame, in which a terrorist is seen as deluded.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, information was given regarding their motives, which were mostly ideological, but also more mental and personal than for men. These findings correspond to the framing modes described by Nacos (2005) and Conway and McInerney (2012), regarding how the media portrays female terrorists. More specifically, two main framing modes are salient for our findings: The family connection frame, emphasizing familial status; and the bored, naive, out-of-touch-with-reality frame, in which a terrorist is seen as deluded.…”
Section: Discussionsupporting
confidence: 84%
“…These frames are specific to the female terrorist, and mainly either garner compassion for her by personalizing her actions, or dismiss the meaningfulness of her actions by depicting them to be greater than her. Conway and McInerney (2012) analyzed the media coverage of two similar terrorist events -one carried out by a female offender and the other by a male offender. They found that the use of the above frames was significantly more prevalent in coverage of the female terrorist's event.…”
Section: News Coverage Of Female Perpetrators' Acts Of Violencementioning
confidence: 99%
“…Although examples of famous and historically important female terrorists exist ( 2 , 3 ), there is still a common tendency to assume that women in general will play more minor, subservient roles than men in terrorist groups that personify highly dangerous and aggressive environments. Indeed, current discourse tends to assume that female ISIS (Islamic State) recruits are “lured,” whereas males are “recruited” ( 4 ). Such assumptions, influenced by long-standing cultural and societal norms, come at the expense of attempting to understand terrorist behavior and the immediate operational context in which it plays out.…”
Section: Introductionmentioning
confidence: 99%
“…The gendering of war and the marginalisation of women in war narratives have been noted by many scholars (Conway and McInerney, 2012;Dowler, 1998;Ette, 2008;Ridd, 1987;Segal, 1993). In Western societies, men are traditionally seen as soldiers and heroes of war while women are perceived as being supportive of the male warrior (Dowler, 2002).…”
Section: Women War and Media Narrativesmentioning
confidence: 99%
“…Consequently, gendered news frames depict men and women in starkly different ways (Conway and McInerney, 2012) and as studies have shown, media frames provide central story lines and enable journalists to attribute 'meaning to issues, events and actors involved' (Melkote, 2009:549). Through the use of news frames journalists can select, organise and emphasis 'certain aspects of reality, to the exclusion of others'…”
Section: Mohammadi and Ross 1996: 114)mentioning
confidence: 99%